Thermal Stability of Optically Transparent Alpha-Zirconium Phosphate/Poly(methyl methacrylate) Nanocomposites with High Particle Loading. Issue 4 (May 2017) - Hatanaka, Logan C.; Diaz, Agustin; Wang, Qingsheng; Cheng, Zhengdong; Mannan, M. Sam
Polymeric nanocomposites have gained attention over the past few decades for their enhanced thermal stability and degradation. However, the reactions involved in a polymer nanocomposite can vary significantly from system to system, making it necessary to investigate novel nanofillers in search for more effective materials. Nanocomposites comprised of alpha-zirconium phosphate (ZrP) nanosheets in poly (methyl methacrylate) (PMMA) were prepared with a wide range of nanoparticle loadings (0, 5, 10, and 30 wt.% ZrP in PMMA). The ZrP nanocomposites were characterized using UV-visible spectroscopy (UV-vis), x-ray diffraction (XRD), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Nanocomposites were well dispersed and optically transparent as shown by XRD and UV-vis. However in the UV region, transparent ZrP nanocomposites possessed excellent UV scattering properties, significantly reducing the transmittance of UV-light, while remaining transparent to the visual spectrum. Thermal stability studies using TGA and DTG showed the peak mass loss rate (PMLR) was reduced by 10% and simultaneously shifted to higher temperatures by 41 °C. Since the nanocomposites in this work cover such a large range of ZrP loadings, large amounts of high-temperature residuals were encountered after TGA studies, indicating that the high loading ZrP nanocomposites are largely noncombustible. In addition, DSC studies showed that ZrP content does affect the glass transition temperature, but not enough to limit the application in which ZrP nanocomposites could be used. These results point to ZrP nanocomposites being useful as polymer replacements, behaving like polymers until the event of a fire, in which case they are largely noncombustible.